Monetary policy with non-separable government spending - Haytem Troug (Journal of Applied Economics, 2020)
The significant role of government consumption in affecting economic conditions raises the necessity for monetary policy to take into account the behaviour of fiscal policy and to also take into account how the presence of the fiscal sector might affect the transmission mechanism of monetary policy in the economy. To test for this, we build an otherwise standard New Keynesian model that incorporates non-separable government consumption. The simulations of the model show that when government consumption has a crowding-in effect on private consumption, it will dampen the transmission mechanism of monetary policy, and vice versa. The empirical estimations of the paper also support the theoretical findings of the model, as the panel regressions show that, in OECD countries, government consumption dampens the effect of the policy rate on private consumption. These results are robust to the zero lower bound era.
Keywords: 330; monetary policy; business cycle; joint analysis of fiscal and monetary policy; New Keynesian models